PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 4 MENGWI - Ni Luh Sintya Dewi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
To improve the quality of education requires a mindset that is used as the basis for implementing the curriculum. Mathematics lessons are often considered by students as a subject that is very difficult and scary. Seeing this problem, it is necessary to make improvements so that the learning process becomes better so that it can improve the quality of learning, especially mathematics lessons. One way to increase student motivation and learning outcomes is with varied learning methods, for example problem-based learning models. The Problem Based Learning (PBL) learning model is learning that focuses on students as learners and on authentic or relevant problems that will be solved using all the knowledge they have or from other sources. The aims of this study were: (1) To find out whether the problem-based learning (PBL) learning model can increase the motivation to learn mathematics in class VIII students of SMPN 4 Mengwi. (2) To find out whether the problem based learning (PBL) learning model can improve student learning outcomes in class VIII SMPN 4 Mengwi. From the results of the implementation of the first cycle, it was known that students' learning motivation had increased, before the pre-action only 20% had high category learning motivation in cycle I increased to 50%. The results of cycle II can be seen that the acquisition of student learning motivation results that have reached the target indicator of success, namely ≥70% have high and or very high learning motivation. And the learning outcomes in the pre-action were 20% with an average of 62.5 then in the first cycle it reached 50% with an average of 69 and in the second cycle it reached 95% with an average of 89. Based on the results of the second cycle it can be seen that 95 % of the total number of students who have achieved the KKM and 5% of the total number of students in the class did not reach the KKM